Annotated Checklist of Rhopalocera of Himachal Pradesh, India (Insecta: Lepidoptera) - Lovish Garlani (SHILAP)
The checklist includes all known Rhopalocera species ever recorded in the state of Himachal Pradesh. All previously published literature, research papers, and reference material were referred and a complete bibliographic reference of all the species mentioned in the checklist is incorporated. This checklist covers 437 species, belonging to 184 genera under 19 subfamilies and 6 families. Moreover, a list of doubtful or misidentified Rhopalocera species reported from Himachal Pradesh is also provided with relevant details in the discussion section. Comments on taxonomic insights and distribution are provided for some species and a list of expected Rhopalocera species is also provided in the discussion section.